2006
DOI: 10.1103/physrevb.74.214103
|View full text |Cite
|
Sign up to set email alerts
|

Lifshitz transitions and elastic properties of osmium under pressure

Abstract: Topological changes of the Fermi surface under pressure may cause anomalies in the lowtemperature elastic properties. Our density functional calculations for elemental Osmium evidence that this metal undergoes three such Lifshitz transitions in the pressure range between 70 GPa and 130 GPa. The related elastic anomalies are, however, invisibly weak. The critical pressures considerably exceed the values for recently measured and calculated anomalies in the pressure (P ) dependence of the hexagonal c/a lattice p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 24 publications
4
29
2
Order By: Relevance
“…This result is in contrast to that of ref. 13, where an ETT was found at this point, but in agreement with ref. 14, in which no ETT was reported.…”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…This result is in contrast to that of ref. 13, where an ETT was found at this point, but in agreement with ref. 14, in which no ETT was reported.…”
Section: Methodssupporting
confidence: 91%
“…Theoretical studies of Os have so far also resulted in an inconsistent picture of its high-pressure behaviour. Reports of possible single or multiple anomalies in c/a ratio at pressures ranging from 9 GPa to over 25 GPa have been both attributed 3 and not attributed 12 to ETT; one study 13 found evidence for multiple ETTs at pressures up to 130 GPa that did not affect the compressional behaviour of Os, and a further study 14 concluded that there are no peculiarities in the pressure-driven evolution of the atomic and electronic structure of Os. The inconsistencies in the theoretical highpressure behaviour of Os mirror the difficulties encountered when probing the high-pressure behaviour of 3d hcp metals such as Zn and e-Fe (refs [15][16][17][18][19].…”
mentioning
confidence: 95%
“…They suggested that the anomaly manifests itself only at finite temperatures due to the anisotropy in thermal expansion coefficients, whereas DFT describes the ground state at T = 0. We suspect that one of the reasons for this is that in hcp Os the value of the DOS (E F ) is smoothly dependent on the pressure even across the ETT [36]. In our case these changes are more conspicuous [see Fig.…”
Section: Elastic and Magnetic Propertiesmentioning
confidence: 68%
“…In this 2.5 electronic phase transition [53][54][55][56][57][58][59][60] the system is in the verge of a first order phase transition, with the possible appearance of a tricritical point. Phase separation has been observed experimentally and several theoretical models have been proposed [61][62][63][64] involving lattice, charge and spin fluctuations near a lattice instability for structural phase transitions [41][42][43].…”
Section: Introductionmentioning
confidence: 99%